2011
DOI: 10.17221/1560-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effect of swim-up purification and incubation of cells on sperm viability in dogs of different ages

Abstract: ABSTRACT:The influence of selected semen extenders on the motility of frozen-thawed dog spermatozoa has been clearly demonstrated in several studies, although there are no reports indicating the effect of swim-up purification on sperm viability in this species of mammals. Therefore, this study was aimed at investigating phosphatidylserine (PS) externalization and necrosis in sperm after variable lengths of time of in vitro incubation after swim-up purification. Dog semen samples were collected from (i) ten dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…In the last decade, a wide variety of sperm selection methods has been developed, which vary greatly in the recovery rate and sperm quality (motility, morphology, chromatin integrity, viability and acrosome integrity) of the samples obtained (Morrell and Rodriguez-Martinez 2011). The techniques that have been used to prepare canine spermatozoa for assisted reproductive techniques (ART) include sperm washing (Rijsselaere et al 2002), swim-up (Bukowska et al 2011;Sa ´nchez et al 2011), density-gradient centrifugation (Kim et al 2010;Dorado et al 2011aDorado et al , 2011bPhillips et al 2012), single-layer centrifugation (SLC; Morrell et al 2008;Dorado et al 2013aDorado et al , 2013bMorrell et al 2013) and glass-wool filtration (Kim et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, a wide variety of sperm selection methods has been developed, which vary greatly in the recovery rate and sperm quality (motility, morphology, chromatin integrity, viability and acrosome integrity) of the samples obtained (Morrell and Rodriguez-Martinez 2011). The techniques that have been used to prepare canine spermatozoa for assisted reproductive techniques (ART) include sperm washing (Rijsselaere et al 2002), swim-up (Bukowska et al 2011;Sa ´nchez et al 2011), density-gradient centrifugation (Kim et al 2010;Dorado et al 2011aDorado et al , 2011bPhillips et al 2012), single-layer centrifugation (SLC; Morrell et al 2008;Dorado et al 2013aDorado et al , 2013bMorrell et al 2013) and glass-wool filtration (Kim et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The sperm migration or swim-up (SU) method is commonly used for the isolation of highly-motile spermatozoa from the ejaculate (Rodriguez-Martinez et al 1997) and can be used for selecting dog spermatozoa to be used in sperm vitrification (Sa ´nchez et al 2011). It has also been reported that the sperm viability in fresh dog semen samples is improved by the SU technique (Bukowska et al 2011). However, the standard SU procedure involves centrifugation steps that induce a decline in motility of spermatozoa (Alvarez et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Из эпидидимиса выделяли сперматозоиды, количество которых подсчитывали в камере Горяева [18], определяли их жизнеспособность [19], индекс DFI (фрагментация ДНК) [20], число апоптотических и некротических сперматозоидов по [21] и содержание фруктозы в семенных пузырьках [22].…”
Section: материал и методыunclassified
“…Sperm motility is one of the most important parameters analyzed in a breeding soundness evaluation because it reflects the ability of sperm to migrate through the female reproductive tract (Bukowska et al, 2011). Sperm motility is also an essential parameter to consider when evaluating the efficiency of extenders, cryoprotectants, and freezing protocols (Rijsselaere et al, 2005).…”
Section: Introductionmentioning
confidence: 99%